How the arts heal: a review of the neural mechanisms behind the therapeutic effects of creative arts on mental and physical health - Barnett, Kelly Sarah; Vasiu, Fabian (Frontiers in Behavioral Neuroscience, 2024)
Background: The creative arts have long been known for their therapeutic potential. These modalities, which include dance, painting, and music, among others, appear to be effective in enhancing emotional expression and alleviating adverse physiological and psychological effects. Engagement in creative arts can be pursued as a personal hobby, in a classroom setting, or through a formal therapeutic intervention with a qualified therapist. Engagement can be active (i.e., creating) or passive (i.e., viewing, listening). Regardless of the modality and manner of engagement, the mechanisms explaining the therapeutic efficacy of creative arts remain poorly understood. Objective: This study aims to systematically review research investigating the neurological mechanisms activated during active or passive engagement in creative arts, with a specific emphasis on the roles of the medial prefrontal cortex (mPFC) and the amygdala in emotional regulation (ER) and creative behaviors. The review seeks to provide preliminary evidence for the possible existence of common neural mechanisms underlying both phenomena, which could inform the development of targeted therapeutic interventions leveraging creative arts for ER. Methods: A systematic review was conducted following the Cochrane Collaboration guideline and PRISMA standards to identify studies examining the neurological mechanisms underlying creative activities. Results: A total of 6 out of 85 records meet the inclusion criteria, with all being basic research studies. Preliminary findings suggest that active and passive engagement with creative arts consistently activate neural circuits implicated in adaptive emotional regulation, including the mPFC and amygdala. These activations mirror the neural pathways engaged in effective ER strategies, suggesting the possible existence of shared mechanisms between creative expression and emotional processing. Conclusion: The evidence underscores the potential of creative arts as a complementary therapeutic strategy alongside conventional care and other evidence-based mind-body modalities. By elucidating the shared neural mechanisms between creative arts engagement and ER, this review contributes to the theoretical and practical understanding of the role of creative arts in mental health. Future research is recommended to further explore these neural correlations and their implications for therapeutic practice.